Parent–Child Relationships Among African Immigrant Families in Canada. Issue 4 (28th May 2020) - Salami, Bukola; Alaazi, Dominic A.; Yohani, Sophie; Vallianatos, Helen; Okeke‐Ihejirika, Philomina; Ayalew, Tesfaye; Nsaliwa, Christina
Abstract : Objective: To examine the factors that influence parent–child relationships in African immigrant families in Alberta, Canada. Background: African immigrants are increasingly migrating to high‐income countries, including Canada, in search of a better life. These immigrants often face several challenges, including parenting their children in new sociocultural contexts. We present findings from a critical ethnographic study of parent–child relationships among African immigrants in Alberta, Canada. Method: Informed by transnational feminist theory, we conducted interviews with 14 African immigrant community leaders, 31 African immigrant parents, and 12 service providers and policymakers. Results: We found that conflicting cultural practices and value systems, shifting power relations, low socioeconomic status, and gender relations exert both beneficial and strenuous influences on parent–child relations. Conclusion: The determinants of parenting practices and parent–child relationships include the intersecting influences of gender, social class, culture, and changing power relations across transnational spaces. Implications: Our findings suggest several policy and practice implications. In particular, we suggest a need to attend to diverse determinants of child well‐being, including income, gender relations, culturally sensitive service delivery, and changing power relations across transnational spaces.